2020
DOI: 10.1139/bcb-2018-0230
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E2 modulates cell cycle function to promote proliferation in pancreatic cancer cells via regulation of the c-Myc–p21Waf1signalling pathway

Abstract: Apolipoprotein E2 (ApoE2) is reportedly critical for cell proliferation and survival, and has been identified as a potential tumour-associated marker in many kinds of cancer. However, studies of the function and mechanisms of ApoE2 in pancreatic cancer proliferation and development are rare. In this study, we performed an analysis to determine the modulatory effects of ApoE2–LRP8 (lipoprotein receptor-related protein 8) pathway on cell cycle and cell proliferation, and explored its mechanisms in pancreatic can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Furthermore, LRP8 was repressed by miR-1262, and overexpression of LRP8 obviously elevated cell growth and tumor progression in breast cancer [14] . In contrast, LRP8 is downstream of apolipoprotein E2, which promotes cell growth and reduces cell apoptosis by activating the phosphorylation of extracellular signal‐regulated kinase (ERK)−1/2 signaling in pancreatic cancer cells [27] . Unfortunately, the biological role of LRP8 in ovarian cancer development remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, LRP8 was repressed by miR-1262, and overexpression of LRP8 obviously elevated cell growth and tumor progression in breast cancer [14] . In contrast, LRP8 is downstream of apolipoprotein E2, which promotes cell growth and reduces cell apoptosis by activating the phosphorylation of extracellular signal‐regulated kinase (ERK)−1/2 signaling in pancreatic cancer cells [27] . Unfortunately, the biological role of LRP8 in ovarian cancer development remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…13 Additionally, we found that ApoE2 was overexpressed in pancreatic cancer tissues, and further results indicated that ApoE2 was essential for cell proliferation and cell cycle progression in pancreatic cancer cells. 14 In this study, we explored the role of ApoE2 in pancreatic cancer migration and invasion and the underlying mechanism. We found that ApoE2 overexpression induced significant enhancements in the cell migration and invasion capacities of pancreatic cancer cells and accelerated the EMT process.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Our previous study demonstrated that ApoE2 could activate ERK1/2 signaling in pancreatic cancer cells. 14 In the present study, we explored whether the AKT, ERK1/2 and JNK signaling pathways were involved in the ApoE2-mediated promotion of the cell migration and invasion of PANC-1 cells. We found that of the three kinases mentioned above, the level of phosphorylated ERK1/2 was significantly increased in a time-dependent manner after treatment of the cells with rhApoE2 ( Figure 5A).…”
Section: Apoe2 Promoted Cell Migration and Invasion Through Activatiomentioning
confidence: 99%
See 2 more Smart Citations